KONTRIBUSI PESANTREN DALAM AKTUALISASI NILAI KEIMANAN, KETAQWAAN, DAN AKHLAK MULIA SELARAS DENGAN AMANAT PASAL 31 AYAT (3) UUD 1945 - Siti Nur Kamila; Muhammad Abdul Roziq Asrori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to describe the process of education in islamic boarding schools in actualizing the values of faith, piety, and noble character, as well as analyzing the contribution of learning practices and habitutation basad on yellow books, quranic memorization, binadzor, and varios islamic activites in forming noble character at Al Fattahiyyah islamic boarding school. This research is motivated by the importance of the role of islamic boarding school as islamic educations institutions to support national education goals as mandated in Article 31 paragraph (3) of the 1945 constution, which emphasizes the importance of faith, piety, and noble character. This research uses a qualitative approach with a case study method. Data were obtained through interviews, observation, and documentation involving several parties of the boarding school including the head of the boarding school, administration, teachers, student, alumni, and the community around the boarding school. Data analysis was conducted through data reduction, data presentation, and drawing conclusion, while the validity of the data was through triangulation of sources and techniques. The result of this study show that the actualization of what is contained in article 31 pharagraph (3) is carried out through the intregation of formal and non formal education supported by varios activites, ranging from congregation prayers, tahfidz Al Qur’an, binadzor, madrasah diniyah, regular recitation of yellow book. This learning system contributes to creating student character that is religious, disciplined, responsible, and possesses noble character. Thus, Al Fattahiyyah Islamic Boarding School plays an important role in implementing the mandate in Article 31 paragraph (3) through the formation of caracters who are faithful, pious, and have noble chracter.